Self-efficacy of employee trainers: Do differences in background characteristics matter? - Raphael Papa Kweku Andoh; Rebecca Dei Mensah; Emmanuel Essandoh (Cogent Business & Management, 2023)
While the self-efficacy literature reveals that demographic or background characteristics of trainers affect their self-efficacy, the focus is mostly on teachers, pre-service teachers and university professors. The demographics characteristics and employee trainers' self-efficacy have received much less attention. The context-specific nature of self-efficacy implies that findings from the aforementioned studies may not be applicable to the employee trainers' context. Thus, this study examined differences in the background characteristics and self-efficacy of employee trainers. Internal employee trainers from two universities in Ghana provided the data for this study. Analyses of the data were done using Mann-Whitney U and Kruskal Wallis tests. The findings of the study demonstrated that a significant difference existed between the instruction self-efficacy of trainers who had non-terminal degrees and trainers who had terminal degrees. Moreover, differences existed in the trainee engagement self-efficacy and instruction self-efficacy across trainers' experiences. Thus, individuals with experience in training should be the first to be considered when selection for employee trainers is being done. Also, for training topics that are quite complex and advanced, trainers with the most advanced degrees ought to be assigned because they would have high instruction-efficacy that would enable them to successfully accomplish such training tasks.
Keywords: 650; demographics; employee trainer; human resource development; learning and development; self-efficacy; workplace training